Beyond the Post-development: Progress Towards a Sustainable Cooperation - Jiménez-Castillo, Manuel Antonio (Sociedad y Economía, 2016)
In this article we aimed to refute the authority of post-structuralist discourse as an alternativeto development. Using the analytical framework of the capabilities approach, we corroboratedhow from the concept of development as freedom can be overcome, withoutabandoning the epistemic relativism of post-developmentalism, the analytical reductionismof contemporary theories of development. Such analysis concludes that capabilities theory,in comparison with post-modern thesis, is not only more coherent normatively, but it canalso be technically operative. To such end, original concepts such as “soft action” and “developmenttrap” are incorporated to overcome, analytically, some of the empirical barriers(mainly commodity fetishism) that may interfere the success of a (sustainable) cooperationframework adapted to the challenges of development as freedom.